Sturm and the Town Hall. A German architecture teacher corrects the work of Jacob van Campen and Jacob Roman (Bulletin KNOB, 2001)
The Amsterdam Town Hall (1648-1665) of Jacob van Campen was undoubtedly one of the major architectonic attractions of the Dutch Republic. Among the many tourists honouring the building with a visit was the North-German architect Leonhard Christoph Sturm (1669-1719), teacher at the Ritterakademie of Wolffenbüttel, who had a large number of treatises on architecture to his name and reported on his findings during his travels in the Netherlands and France in 1697, 1699 and 1712 in his Architectonische Reiseanmerkungen, which appeared in the year of his death.Among the many buildings in the classicist building style, which he described and criticised there, were also a few town halls, a theme to which Sturm devoted a separate text in 1718. Three of them are entered into more extensively: besides the Amsterdam Town Hall, the Delft Town Hall (1618-1620) of Hendrick de Keyser and the Deventer Town Hall (1686-'88) of Jacob Roman.The Delft Town Hall is denounced as too extravagant; of the Deventer Town Hall Sturm made a far from perfect elevation drawing of the facade on the basis of flawed sketches and memories, for which he subsequently proposed some improvements that had actually already been realised in the building.Nor is the Amsterdam Town Hall spared, in which the absence of a monumental entrance section particularly annoys him, besides a few minor 'shortcomings'. He was not the only one; many foreign travelers felt the same, before as well as after him. However, unlike them, Sturm drew an alternative floor plan, in which instead of the seven low semi-circular arches he had designed a grand staircase, possibly inspired by Vingboons' alternative design for the town-hall, which in his view was indispensable for the town hall of such a large town.In the German treatises he more or less constituted a standard element in theory, although in practice he was mostly absent in the German towns. Furthermore, without commenting on it, the author - without being aware of it? - made some more corrections in the floor plan, such as increasing the number of windows in the side wall by one window, thus producing an odd number, which gave him the opportunity to highlight the central axis.The Amsterdam Town Hall did not only function as a source of inspiration for Sturm in his treatise on town halls. In his Ausführliche Anleitung zur Bürgerlichen Baukunst his younger colleague Johann Friedrich Penther (1693-1749) commended it as the most important specimen of the century, serving as a guiding principle for himself, too, in the relevant chapter of his manual, where he, just as Sturm, presents a few of his own designs for town halls.